Interdependenţa dintre erodarea imunităţii suverane și ascensiunea vulture funds / The Nexus between Sovereign Immunity Erosion and the Rise of Vulture Funds - Alexandru CHISTRUGA (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice)
Sovereign immunity posed a significant barrier to the rise of vulture funds. Until the mid-20th century, U.S. courts adhered to the doctrine of absolute sovereign immunity, which shielded debtor states from lawsuits brought by private creditors. However, in 1952, the U.S. Department of State introduced the doctrine of restrictive sovereign immunity, arguing that foreign states should not be immune from jurisdiction when they are involved in commercial activities. In the absence of clear legislation defining „sovereign immunity” and „commercial activity” it fell to the courts to interpret the intentions of the Department of State. Therefore, this paper will focus on how U.S. courts have defined the concept of commercial activity and trace the key developments that led to the erosion of sovereign immunity, ultimately facilitating the rise of vulture funds.